Changes in uses of salutations in British English - Hassan, Ahdi; Mitchell, Rod; Buriro, Hakim Ali (International research journal of management, IT and social sciences, 2020)
As is only natural, British English has undergone a change in its use of salutations. An important question is whether there has been significant influence from immigrants and/or other varieties of English on how British salutations are used, and, if so, how this is realised. We approach the analysis by evaluating how salutations have evolved and are evolving in appropriateness in spoken and written contexts. A finding from the data is that polite salutations appear to be becoming more generalized, i.e. more neutral. This paper draws on data from contemporary English in social, academic and YouTube texts, in both in formal and informal spoken and written contexts, as well as from the last few decades, exploring social, cultural and pragmatic meanings of salutations, with attention given to academic, social and stylistic uses such as when addressing strangers or the humorously ironic.